COLLAGEN AND BIOACTIVE PEPTIDES FROM HULU'U FISH SCALES AND GILLS (GIURIS MARGARITICUS) AS POTENTIAL AGENTS FOR DIABETIC WOUND THERAPY - Wiwit Zuriati Uno; Siti Naysila; Adelin Salsahbila Usman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aimed to explore collagen content and bioactive peptides derived from scales and gills of endemic upstream fish from Gorontalo, to evaluate their antioxidant activity, fibroblast proliferation stimulation in vitro, and antidiabetic potential through inhibition of ?-glucosidase and ?-amylase enzymes, supporting the development of local diabetic wound therapy agents. Fish scales and gills were dried, ground, and extracted using acetic acid. Collagen was precipitated, dried, and hydrolyzed with pepsin to obtain peptides <10 kDa. Collagen content was determined using a hydroxyproline assay. Antioxidant activity was evaluated using DPPH and ABTS assays. Fibroblast proliferation was assessed by a scratch assay under hyperglycemic conditions (25 mM glucose). Antidiabetic potential was examined through in vitro inhibition of ?-glucosidase and ?-amylase. Results showed that collagen content in scales was higher than in gills. Both extracts exhibited significant antioxidant activity, enhanced fibroblast proliferation, and demonstrated inhibitory effects on ?-glucosidase and ?-amylase. These findings indicate that fish scales and gills are promising sustainable biomaterials for diabetic wound therapy and local pharmaceutical innovation.